Peripheral blood cytokines as potential diagnostic biomarkers of suicidal ideation in patients with first-episode drug-naïve major depressive disorder - Xu, Yayun; Liang, Jun; Gao, Wenfan; Sun, Yanhong; Zhang, Yuanyuan; Shan, Feng; Ge, Jinfang; Xia, Qingrong (Frontiers in Public Health, 2022)
Objective: Major Depressive Disorder (MDD) is a leading cause of disability, with a high risk of suicidal ideation (SI). Few studies have evaluated the potential of multiple cytokines as biomarkers for SI in patients with MDD. In the present study, we examined the serum levels of multiple cytokines in patients with first-episode drug-naïve MDD, with the aim to discover and identify serum cytokines-based biomarkers for identification of SI in MDD. Methods: A total of 55 patients with first-episode drug-naïve MDD were enrolled and divided into two groups: 26 MDD patients without SI and 29 MDD patients with SI. Beck Scale for Suicide Ideation was used to estimate SI. A total of 37 cytokines were measured using Multiplex Luminex Assays. The levels of serum cytokines between MDD patients without SI and MDD patients with SI were compared and diagnostic values of different cytokines were evaluated using the receiver operating characteristic (ROC) curve method for discriminating MDD patients with SI from MDD patients without SI. The relationship between the group and the abnormal cytokines were investigated in multiple linear regression models, with adjustments for age, gender, BMI, smoking, and Hamilton Depression Rating Scale-24 (HAMD-24) scores. Results: The levels of CCL26 and VEGF in MDD patients with SI were significantly lower than those in MDD patients without SI (all P < 0.05). On the contrary, the levels of IL-17C, CXCL10, and TNF-β in MDD patients with SI were significantly higher than those in MDD patients without SI (all P < 0.05). Moreover, the results of multiple linear regression revealed that group was a significant independent predictor of serum IL-17C, CCL-26, VEGF, and TNF-β levels (all P < 0.05). Furthermore, the AUC values of IL-17C and TNF-β were 0.728 and 0.732, respectively. Additionally, a combined panel of IL-17C and TNF-β achieved a high accuracy in discriminating MDD patients with SI from MDD patients without SI (AUC = 0.848, sensitivity = 75.9%, specificity = 72.7%). Conclusions: These results suggested that circulating IL-17C and TNF-β may hold promise in the discovery of biomarkers for identification of SI in MDD.